2, 4‐DCP compromises the fertilization capacity of mouse oocytes. Issue 11 (30th April 2021) - Dai, Xiaoxin; Qiu, Lijun; Rashida, Churi; Xu, Chunying; Mu, Yi; Gao, Yang; Chu, Zhangjie; Zhao, Bo
Abstract: 2, 4‐DCP (2, 4‐dichlorophenol) is an environmental estrogen that is ubiquitously distributed in the environment and widely used to produce herbicides and pharmaceutical intermediates. Although 2, 4‐DCP is suspected to have endocrine disruption, the reproductive toxicity of 2, 4‐DCP in mammals has not been adequately assessed. In the present study, we examined the effect of 2, 4‐DCP on the fertility of mouse eggs. The data showed that oral administration of 2, 4‐DCP (180 mg/kg/day for 7 days) compromises the fertilization rate of mouse oocytes. To further analyze the mechanism by which 2, 4‐DCP decreases fertilization, the key regulators and events during fertilization of mouse eggs were investigated. We found that the dynamics of cortical granules (CGs) were disrupted by showing the redistribution of CG free domain in 2, 4‐DCP‐administered oocytes. This abnormality perturbed the sperm binding site in the zona pellucida (ZP) and dramatically reduced the number of sperm binding to the ZP of 2, 4‐DCP‐administered oocytes. In addition, the abundance of Juno, a sperm receptor on the egg membrane, was also decreased and its distribution was mislocated in 2, 4‐DCP‐administered oocytes. Finally, we validated that the defects of fertilization participants and events caused by 2, 4‐DCP might be mediated by the increased level of reactive oxygen species‐induced apoptosis of oocytes. Therefore, we demonstrate that 2, 4‐DCP compromises the fertilization ability of mouse oocytes via inducing oxidative stress. Abstract : 2, 4‐DCP (2, 4‐dichlorophenol) is an environmental estrogen that is ubiquitously distributed in the environment and widely used to produce herbicides and pharmaceutical intermediates. Although 2, 4‐DCP is suspected to have endocrine disruption, the reproductive toxicity of 2, 4‐DCP in mammals has not been adequately assessed. We validated that the defects of fertilization participants and events caused by 2, 4‐DCP might be mediated by the increased level of reactive oxygen species‐induced apoptosis of oocytes.